The conceptual review of Islamic shariah based financing for the student in the Higher Education Institutes (HEIs) / Effuandy Pfordten Md Saleh … [et al.] - Md Saleh, Effuandy Pfordten; Ali, Md. Jafor; Sabli, Norhaila; Huda, Md. Nazmul; Uddin, Md. Kamal (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Quality Higher Education transforms human life into meaningful human resources. Moreover, it brings qualitative changes in humankind and socioeconomic development with the help of extended knowledge and higher skills. But, many devout Muslims struggle with traditional student financing, as interest (riba) is impermissible in shariah. This study aims to review the options of the student financing concepts based on the shariah perspective and evaluate the associated issues with its application. The present qualitative study will be adopted mostly from primary and secondary sources of shariah such as Quran, Hadith, Islamic Jurisprudence, and Islamic scholars ’ views. The deliberations evolve at reviewing the shariah concept of Quard-al-hasanah, Quard-bill-ujrah, waqf (Islamic trust), and takaful. Finally, the present study highlights that the higher education financing based on the shariah concept could also be generalized into shariah-based financing that would interest (riba) free and acceptable to the Muslim community at large.